Systems Genetics Approaches in Rat Identify Novel Genes and Gene Networks Associated With Cardiac Conduction. Issue 21 (6th November 2018) - Adriaens, Michiel E.; Lodder, Elisabeth M.; Moreno‐Moral, Aida; Šilhavý, Jan; Heinig, Matthias; Glinge, Charlotte; Belterman, Charly; Wolswinkel, Rianne; Petretto, Enrico; Pravenec, Michal; Remme, Carol Ann; Bezzina, Connie R.
Abstract : Background: Electrocardiographic (ECG) parameters are regarded as intermediate phenotypes of cardiac arrhythmias. Insight into the genetic underpinnings of these parameters is expected to contribute to the understanding of cardiac arrhythmia mechanisms. Here we used HXB/BXH recombinant inbred rat strains to uncover genetic loci and candidate genes modulating ECG parameters. Methods and Results: RR interval, PR interval, QRS duration, and QTc interval were measured from ECGs obtained in 6 male rats from each of the 29 available HXB/BXH recombinant inbred strains. Genes at loci displaying significant quantitative trait loci (QTL) effects were prioritized by assessing the presence of protein‐altering variants, and by assessment of cis expression QTL (eQTL) effects and correlation of transcript abundance to the respective trait in the heart. Cardiac RNA‐seq data were additionally used to generate gene co‐expression networks. QTL analysis of ECG parameters identified 2 QTL for PR interval, respectively, on chromosomes 10 and 17. At the chromosome 10 QTL, cis ‐eQTL effects were identified for Acbd4, Cd300lg, Fam171a2, and Arhgap27 ; the transcript abundance in the heart of these 4 genes was correlated with PR interval. At the chromosome 17 QTL, a cis ‐eQTL was uncovered for Nhlrc1 candidate gene; the transcript abundance of this gene was also correlated with PR interval. Co‐expression analysis furthermore identified 50 gene networks, 6 of which were correlated with PR interval or QRS duration, both parameters of cardiac conduction. Conclusions: These newly identified genetic loci and gene networks associated with the ECG parameters of cardiac conduction provide a starting point for future studies with the potential of identifying novel mechanisms underlying cardiac electrical function.